2021
DOI: 10.1108/pijpsm-06-2021-0078
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on police training academies

Abstract: PurposeThe purpose of this study is to explore the impacts coronavirus disease 2019 (COVID-19) had on US police academies’ production of police recruits.Design/methodology/approachThe study used a national online survey of police academy directors in the USA, followed by purposive, semi-structured interviews of select academy directors. A combination of quantitative and qualitative data is combined in a mixed methods approach.FindingsThe findings suggest that academies experienced a range of impacts related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, since the emergence of COVID-19 in the U.K there has been no detailed examination of how it affected the area of training within policing. What literature does exist within policing has focused on academies training new recruits (White et al, 2021), or is unempirical in nature (Fuchs, 2021). Instead, research has focussed on overall crime rates which have been examined in the United States (Boman and Gallupe, 2020), Australia (Payne et al, 2020) and the United Kingdom, and identified that crime rates reduced significantly (Halford et al, 2020).…”
Section: The Impact Of Covid-19 On Teaching and Educationmentioning
confidence: 99%
“…However, since the emergence of COVID-19 in the U.K there has been no detailed examination of how it affected the area of training within policing. What literature does exist within policing has focused on academies training new recruits (White et al, 2021), or is unempirical in nature (Fuchs, 2021). Instead, research has focussed on overall crime rates which have been examined in the United States (Boman and Gallupe, 2020), Australia (Payne et al, 2020) and the United Kingdom, and identified that crime rates reduced significantly (Halford et al, 2020).…”
Section: The Impact Of Covid-19 On Teaching and Educationmentioning
confidence: 99%
“…Two articles in this issue focus on how police practices were impacted or adapted due to the pandemic. White et al . (2021) use a mixed methods approach to understand the challenges faced by police training activities.…”
Section: In This Issuementioning
confidence: 99%
“…Two articles in this issue focus on how police practices were impacted or adapted due to the pandemic. White et al (2021) use a mixed methods approach to understand the challenges faced by police training activities. They collected data from a national online survey (n 5 127) of police academy directors in the USA and then followed up with semi-structured interviews (n 5 19).…”
Section: Effects On Police Practicesmentioning
confidence: 99%
“…Given 90% of the population in the United States were under the effect of stay-at-home orders (White and Fradella, 2020), understanding the experiences of those agencies as they served their communities is vital to a more holistic picture of policing during the pandemic. There is also a collateral need to document the experiences of police agencies to better understand and isolate areas for improvement and pathways to more effective collaborations in response to future public health emergencies (White et al ., 2021; Jones, 2020),…”
mentioning
confidence: 99%
“…Given 90% of the population in the United States were under the effect of stay-at-home orders (White and Fradella, 2020), understanding the experiences of those agencies as they served their communities is vital to a more holistic picture of policing during the pandemic. There is also a collateral need to document the experiences of police agencies to better understand and isolate areas for improvement and pathways to more effective collaborations in response to future public health emergencies (White et al, 2021;Jones, 2020), To enhance "lessons learned", this research captures the organizational and operational experiences of police departments in the state of Washington across two waves of survey administration. It is in part a state-specific replication of the IACP instrument fielded by Lum et al (2020a) on the experiences of police departments working under COVID-19.…”
mentioning
confidence: 99%